Scenario Modeling of Thermal Influence from Forest Fire Front on a Coniferous Tree Trunk; MATEC Web of Conferences; Vol. 72 : Heat and Mass Transfer in the System of Thermal Modes of Energy – Technical and Technological Equipment (HMTTSC-2016) - Baranovskiy N. V. Nikolay Viktorovich (2016, 2016)
Title screen